Molecular Epidemiology and Antimicrobial Resistance of Methicillin Resistant Staphylococcus aureus (MRSA) from Milk and Nasal Samples of Dairy Buffalos in Nueva Ecija, Philippines - Alona Torres Badua (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Methicillin Resistant Staphylococcus aureus (MRSA) is a zoonotic pathogen that carries the mecA gene responsible for the loss of susceptibility to methicillin and other βlactam antibiotics. Only MRSA human rate has been reported in the Philippines and baseline